2016
DOI: 10.3174/ajnr.a4957
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Assessment by CT Angiography as a Predictor of Outcome in Symptomatic Cervical Internal Carotid Artery Occlusion

Abstract: Assessment of collateral circulation with CTA can be a useful predictor of 3-month outcome in patients with symptomatic cervical ICA occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…In contrast, in Sundaram's study, among patients suffering intracranial carotid artery occlusion, the odds of a favorable outcome at 90 days after onset was higher in the group with ipsilateral ophthalmic artery or leptomeningeal collaterals than in those with a complete Willis' circle (Sundaram, Kannoth, Thomas, Sarma, & Sylaja, ). However, in their study, they included patients who were up to 3 weeks after onset, and their patients differed from candidates for EVMT.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, in Sundaram's study, among patients suffering intracranial carotid artery occlusion, the odds of a favorable outcome at 90 days after onset was higher in the group with ipsilateral ophthalmic artery or leptomeningeal collaterals than in those with a complete Willis' circle (Sundaram, Kannoth, Thomas, Sarma, & Sylaja, ). However, in their study, they included patients who were up to 3 weeks after onset, and their patients differed from candidates for EVMT.…”
Section: Discussionmentioning
confidence: 82%
“…Several methods, including CTA (Sundaram et al, ; Yeo et al, ) and MR (Alves et al, ), have been established to evaluate collateral status. Although CTA is highly accurate in the assessment of anatomical variations of Willis' circle, its sensitivity remains limited in its ability to reveal hypoplastic segments (Han et al, ), and time‐of‐flight (TOF) MRA has disadvantages in a setting involving slow flow at the site of occlusion, which often results in complete loss of the signal in arteries and the consequential underestimation of collateral status (Raymond & Schaefer, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following CTO of the ICA, perfusion pressure at the vascular occlusion is decreased ( 27 ). In response to the deficient blood supply from main arteries, the cerebral blood flow (CBF) immediately establishes collateral circulation; this involves immediate diversion of blood flow in the event of large-vessel occlusion, as well as chronic compensation by secondary collaterals such as the ipsilateral ophthalmic artery, ipsilateral posterior communicating artery, anterior communicating artery and pia mater collaterals ( 28 ). Effective leptomeningeal collateral circulation and the presence of more than 2 collaterals have been associated with good clinical condition without severe disability ( 28 ).…”
Section: Hemodynamicsmentioning
confidence: 99%
“…Their results are consistent with our grading system. Sundaram et al (14) found that patients with 2 or more collaterals (ipsilateral OA, ipsilateral PCOM, ACOM, and Leptomeningeal collaterals) had excellent outcomes, indicating that as more collaterals were recruited, thus providing an effective compensatory mechanism. This finding is partially consistent with our grading system as more than 2 collaterals are important for maintaining adequate cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%